TAUHID HERMENEUTICS OF FAḤRUDDIN AL-RᾹZI: A STUDY ON THE INTERPRETATION OF SURAH AL-IKHLᾹS IN THE MAFᾹTIḤ AL-GAῙB - Lukman Fajariyah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
The Qur'ān is a way of life that is always mined and studied to answer the complex and dynamic problems of life. The works of interpretation are one of the proofs of interpretation products dedicated by interpreters of the ulama to succeed in the effort to understand the Qur'ān so that it can be guided and truly become the way of life. Efforts to understand the Qur'an are carried out with a variety of approaches and methods, one of which is the hermeneutic method. The Mafātiḥ al-Gaīb interpretation by Faḥruddin Al-Rāzi is a representation of interpretation that applies hermeneutic elements. This paper aims to explore the elements of hermeneutics in Mafātiḥ al-Gaīb's interpretation by Faḥruddin Al-Rāzi by taking a sample of Al-Ikhlās's letter. The research method used in this study is a qualitative descriptive method, the authors attempt to examine and describe the data that exists. The findings in this study indicate that the hermeneutic elements used by Al-Rāzi in the interpretation of Al-Ikhlās include munāsabah, asbāb an-nuzūl, and esoteric meanings. The three components are used to find out the meaning of an objective and comprehensive text from Surah Al-Ikhlās. So that it concludes that the essence of God referred to in Surah Al-Ikhlās includes His żat, ṣifat, and af’al.